The Importance of Animacy-Inanimacy Category of the Noun and the Context - Narushevich, Andrey (Slavica, 2020)
The article considers the semantic aspect of the of animacy-inanimacy category in nouns in Russian language, in particular, peculiarities of collocability of some nouns with verbs in terms of animacy-inanimacy category.The study of the semantic interaction of nouns and animate-inanimate marked verbs, which are collocating with these nouns, allows to detect combination of signs of “animate” or “inanimate” in meanings of some nouns with fluctuant grammatical indicator of animacy-inanimacy category. Thus, this study can raise the issues about the cognitive factor in meaning formation process and also about specific character of the process how peculiarities of cognitive experience, received from human exploration of the environment, are expressed.